2012
DOI: 10.1093/jxb/ers255
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cellulose synthase genes from domesticated apple identifies collinear genes WDR53 and CesA8A: partial co-expression, bicistronic mRNA, and alternative splicing of CESA8A

Abstract: Cellulose synthase (CesA) genes constitute a complex multigene family with six major phylogenetic clades in angiosperms. The recently sequenced genome of domestic apple, Malus×domestica, was mined for CesA genes, by blasting full-length cellulose synthase protein (CESA) sequences annotated in the apple genome against protein databases from the plant models Arabidopsis thaliana and Populus trichocarpa. Thirteen genes belonging to the six angiosperm CesA clades and coding for proteins with conserved residues typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 66 publications
(73 reference statements)
0
10
0
Order By: Relevance
“…Specifically, a plant WDR53 gene (represented by At5g45760 in Arabidopsis ) is collinear with the secondary cell wall CesA8 , while a WDR83 (At5g64730) is adjacent to the primary cell wall CesA6 (schematized in Figure 1D ). We showed that WDR53 and CesA8 are partially co-expressed in apple and Populus ( Guerriero et al, 2012 ). Further, we identified a bicistronic WDR53-CesA8 transcript in phytoplasma-infected apple tissues, where the CesA8 cistron is alternatively spliced and lacks a portion corresponding the RING-type zinc finger domain.…”
Section: Conserved Collinear Microsynteny Between Wdr and Glycan Syntmentioning
confidence: 97%
See 2 more Smart Citations
“…Specifically, a plant WDR53 gene (represented by At5g45760 in Arabidopsis ) is collinear with the secondary cell wall CesA8 , while a WDR83 (At5g64730) is adjacent to the primary cell wall CesA6 (schematized in Figure 1D ). We showed that WDR53 and CesA8 are partially co-expressed in apple and Populus ( Guerriero et al, 2012 ). Further, we identified a bicistronic WDR53-CesA8 transcript in phytoplasma-infected apple tissues, where the CesA8 cistron is alternatively spliced and lacks a portion corresponding the RING-type zinc finger domain.…”
Section: Conserved Collinear Microsynteny Between Wdr and Glycan Syntmentioning
confidence: 97%
“…We have also showed that the genomic association between a WDR gene and a gene encoding a glycosyltransferase from family 2 (GT2) is a conserved feature in eukaryotes, since, besides dicots, it is reported in metazoans (hyaluronan synthase-WDR microsynteny) and in fungi (chitin synthase-WDR microsynteny; Guerriero et al, 2012 ). In fungi, the genomic collinearity between a chitin synthase ( chs ) and a WDR gene is conserved among several species (Guerriero et al, in revision).…”
Section: Conserved Collinear Microsynteny Between Wdr and Glycan Syntmentioning
confidence: 99%
See 1 more Smart Citation
“…We show that FPWD , a gene coding for a WDR protein, is a conserved collinear genomic neighbor of chsD in Ascomycetes. The chsD and FPWD genes, together with a closely linked bf gene, are located within a cell wall metabolic gene cluster recently identified in Aspergilli [ 7 ]. The study identified the fungal wall gene cluster based on the predicted functions of conserved gene neighbors of chsD , which comprise a Chs activator, a myosin V, a GH17 cell wall glucanase, scw11, a serine/threonine kinase, and a type 2A protein phosphatase PP2A.…”
Section: Discussionmentioning
confidence: 99%
“…Previous results showed conserved genomic microsynteny and partial co-expression of a glycosyltransferase from family 2 (GT2, i.e., a cellulose synthase, CesA ) and a WDR gene in plants [ 6 , 7 ], and that the collinear arrangement of genes coding for a GT2 enzyme and a WDR protein is frequent in eukaryotes’ genomes. Here, we show that conserved collinearity of a GT2-WDR gene pair is also present in fungi, where a gene coding for a WDR protein is a conserved gene neighbor of a class IV chitin synthase ( chsD ).…”
Section: Introductionmentioning
confidence: 99%